Embodiment of divine knowledge in early Judaism - Orlov, Andrei A. (Routledge studies in the biblical world, 2022)
Chapter 1: The Divine image as the hypostasis of Divine knowledge -- Chapter 2: The Divine face as the hypostasis of Divine knowledge -- Chapter 3: The Divine name as the hypostasis of Divine knowledge -- Chapter 4: The epistemology of Divine presence and pseudepigraphical attribution.